MY SAY: The true meaning of heritage - Abd Razak, Dzulkifli (2008)
The recent global recognition of Penang and Melaka as part of the Unesco World Heritage List is indeed a hardearned tribute for many Malaysians. It took no less than a decade to clinch this feat; but like they say, to win once is much easier than to keep on winning over and over again. We therefore cannot rest on our laurels if we want to keep this new status forever. The question then: are we, especially the people of the two "sites", ready for this? We now cannot depend any longer on committees or groups of interested persons, but this time, the entire population must be involved. We have no choice and here is where the new challenge begins.